Potassium and Phosphorus Fertilizer Impacts on Alfalfa Taproot Carbon and Nitrogen Reserve Accumulation and Use During Fall Acclimation and Initial Growth in Spring - Berg, W. Kess; Brouder, Sylvie M.; Cunningham, Suzanne M.; Volenec, Jeffrey J. (Frontiers in Plant Science, 2021)
Phosphorus (P) and potassium (K) impact alfalfa (Medicago sativa L.) performance, but how these nutrients alter taproot physiology during fall acclimation and subsequent growth in spring is unclear. Our objectives were to: 1) determine seasonal patterns for taproot P and K concentrations during fall acclimation, and during initial shoot growth in spring; 2) determine how P and K nutrition impacts accumulation of taproot C and N reserves during fall and their subsequent use when shoot growth resumes in spring; and 3) assess how addition of P and K fertilizer impacts accumulation and use of C and N reserves impacts survival and shoot growth in spring. Two P (0 and 75 kg ha-1) and two K (0 and 400 kg ha-1) treatments were applied and taproots were sampled between Sep and Dec, and again from Mar to May over two years. Concentrations of taproot sugar, starch, buffer-soluble protein, amino-N, and RNA pools were determined. While P and K fertilizer application increased taproot P and K concentrations two-to three-fold, concentrations of P and K in taproots over time did not change markedly during cold acclimation in fall, however, taproot P declined in spring as plant growth resumed. Compared to the 0K-0P treatment, taproots of plants fertilized with 400K-75P had higher starch, protein, amino-N, and RNA, but reduced sugar concentrations in fall. Concentrations of all these pools, except starch, declined during the initial two weeks of sampling beginning in late March as shoot growth resumed in spring. Herbage yield in May was highest for the 400K-75P treatment, and least for the 0K-0P treatment; differences that were associated with variation in mass shoot-1 and not shoots m-2. High yield of the 400K-75P plants in May was consistently associated with greater concentrations and use of amino-N, soluble protein, and RNA pools in taproots, and not with accumulation and use of starch and sugar pools. Understanding factors leading to the accumulation of taproot N reserves and RNA during cold acclimation in fall and their use during the initial growth in spring should enhance efforts to improve alfalfa growth and herbage yield in spring.